Pengaruh komposisi CoFe2O4 terhadap sifat listrik nanokomposit CoFe2O4/pani yang disintesis dengan metoda sol-gel (CoFe2O4 composition influence on the electrical properties of the CoFe2O4 / PANI nanocomposite synthesized by the sol-gel method) - Fildzah Rudyah Putri Nurzam; - Ramli; - Ratnawulan (PILLAR OF PHYSICS, 2019)
Nanocomposite ofCoFe2O4-polyaniline (CoFe2O4/PANi) with various variationsCoFe2O4 and PANi 20%, 30%, 35%, 40%, 50% which was synthesized by sol-gel method. Samples are characterized by X-ray difractionandLCR meterwith  CoFe2O4compositions 20%,30%,35%,40% and 50%. Nanocomposites of CoFe2O4/PANi in prepares using sol-gel method wih precursors Fe(NO3)3.9H2O and Co(NO3)2.6H2O with PANi.The Samples the gel shaped thin layer of nanocomposite is characterized usingX –Ray Difraction and LCR meter. The XRD characterization results obtained the crystal size values on the composition variations is 44,86 nm, 39,86 nm, 41,47 nm, 59,65 nm, 57,42 nm  and LCR meter characterization have value is  12,2x10-9 F, 11,2x10-9 F, 10,8x10-9 F, 9,6x10-9 F, 7,3x10-9 F. Variations in composition of nanocomposite CoFe2O4/PANi affect the value of crystal size and electrical properties of nanocomposites CoFe2O4/PANican be applied to  supercapasitor.